Witness at the Cross: A Beginner’s Guide to Holy Friday - Cohick, Lynn H. (Christian scholar's review, 2022)
Witness at the Cross: A Beginner’s Guide to Holy Friday Amy-Jill Levine Published by Abingdon in 2021 176 pp / $17.99 / 9781791021122 Amazon Goodreads I double-checked the title; was...